Sharia Supervisory Board Practices in Conducting Operational Supervision in Sharia Microfinance Institutions - Rosalina, Hamdah; Zakiyah, Fajriya; Rahayu, Adilia; Zam-zamiyah, Frida Tis'a; Ismail, Ade Muhammad; Izharuddin, Rijal (ITQAN: Journal of Islamic Economics, Management, and Finance, 2022)
This research aims to explain the practice of the Sharia Supervisory Board in conducting operational supervision at Baitul Maal wat Tamwil (BMT). This research uses a qualitative approach based on primary data obtained from semi-structured interviews with speakers as a Sharia Supervisory Board in one of Baitul Maal wat Tamwil in Indonesia that already has a certificate as a sharia supervisory board from MUI and has a long track record in conducting Sharia supervision. The analysis is compiled based on transcripts of interviews with the key informants equipped with literature studies as well as related regulations. The results of this study prove that in practice, the Sharia Supervisory Board supervises operations as well as provides understanding through consultation with BMT customers and employees. The result of such supervision is sharia compliance opinions reported to the relevant parties periodically, namely two times a year, and the supervisory mechanism refers to guidelines issued by the DSN-MUI and the Ministry of Cooperatives and SMEs. The competence that must be mastered by the Sharia Supervisory Board is related to its knowledge in the field of contemporary fiqh muamalah as well as transactions contained in the Islamic financial industry. The obstacles faced by the Sharia Supervisory Board in carrying out its duties are the lack of understanding of BMT customers and employees on sharia principles and the absence of specific regulations governing product codification in BMT.